Upaya Peningkatan Branding Produk UMKM Keripik Pisang Berbasis Ekonomi Kreatif Melalui Logo Dan Kemasan - Putri Laili Susanti; Eko Purwanto (JURNAL RISET MANAJEMEN (JURMA), 2023)
Banana Chips UKM is a Micro, Small and Medium Enterprise (MSMEs) engaged in the production of chips in Karangan Village, Bareng District, Jombang Regency. The problem for UMKM Banana Chips is that they don't have logos and packaging that is less attractive. Therefore, there is a need for training and assistance regarding the importance of implementing logos and packaging so that the sales system can attract more consumers, expand the scope of its business objectives and support even better sales activities. This activity aims to increase the knowledge of MSME actors about the importance of creating a product identity. This community service uses surveys and observations, interviews and applications. The results of this community service help create attractive logo designs and product packaging and can strengthen brand identity.